(untitled) (Journal of Health Sciences, 2020)
Introduction: Violence against nurses at the workplace is an alarming problem in both developed and developing countries affecting the quality of their work. The aim of this study is to assess the prevalence of external (patient initiated) and internal violence (initiated by staff members) against nurses and studying the violence-associated factors such as perpetrators, the attitude of nurses following aggression incidents, consequences, and impact on nurses and work. Methods: A cross-sectional study included 385 nurses from three different hospitals in Minia district was agreed to participate in the study. These hospitals included Health Insurance Hospital, Minia University Hospitals (Minia University Gynecological, Obstetric, and Pediatric Hospital and Minia Renal Hospital), and Minia general hospital. The well-structured questionnaire covered four main domains; sociodemographics, lifetime working experience of violence, external and internal violence and its effects on work, the perpetrators of violence, and attitude of nurses following violent incidents. Results: More than half of nurses (55.8%) were exposed to workplace violence during their working lifetime. Experiencing external violence (patient initiated) during the past year was significantly higher (57.4%) than the internal (staff initiated) type (33.5%). Verbal violence was the most common type of violence. Reporting violence incidents were done by 68.3% and 38.7% of the nurses who were exposed to external and internal violence, respectively. Conclusion: Violence against nurses working in different health-care facilities at Minia district was prevalent and has a significant impact on nurses and their work.